Back to work again: Survival analysis of factors promoting return after industrial accidents. - Kang, Dongsuk (Work, 2025)
Backgrounds: Since 2022, South Korea has enacted the "Serious Accident Punishment Act" to enhance the safety of industrial workers. However, serious industrial accidents have continued to occur since the Act's implementation. The COVID-19 pandemic has seen an increase in both the number and severity of these accidents. This highlights the need for better policies to prevent accidents and provide comprehensive medical and social support for injured workers. Objectives: This study examines how different factors (e.g., policies, personal efforts, and demographic factors) affect the time it takes for workers injured in industrial accidents to return to their jobs. Methods: This research utilized the Cox hazards model to examine the factors using data from the Panel Study of Workers' Compensation Insurance (2018–2020). Results: The study found that several factors (e.g., experience with vocational rehabilitation services, living in large cities, having a higher disability rating, and being younger) helped workers return to their jobs more quickly. Conclusions: Our findings suggest that younger workers living in big cities with access to vocational rehabilitation services can return to work faster. This study also emphasizes the need for stronger policies to support older workers in rural areas. As South Korea's population ages and more young people move to cities, these challenges will become even more pressing.